Development of automated system for monitoring ruminant grass environment in vertical farming system - Muhamad Amirul Hafiz, Zahari (2022)
This thesis offers an automated system for monitoring ruminant grass environment in a vertical farming system, which is intended to improve farming techniques and readily involve new farmers or gardeners in the system. More space or land will be required for ruminant grass farms as Malaysia's population continues to rise at a rapid rate. This is due to the larger quantity of land occupied by residential or industrial structures. Ruminant grass farms will cause complications in the future. In order to produce higher yields per square metre of soil, more attention is being dedicated to growing vertical lawns for ruminants. As a result, the major purpose of this project is to develop an automated system for monitoring ruminant grass environment in vertical farming systems that may be used in conjunction with the Internet of Things to track the ruminant grass environment (IoT). The system determines the current status of the environment using various sensors like as temperature and humidity sensors, moisture sensors, and pH sensors, and provides data to the Arduino. After that, the data is processed on the Arduino before being transferred to the Blynk App. The device can track where the equipment is operating, making repairs easier in the event of a malfunction. The Blynk app also features a basic remote control that allows users to tum on and off the irrigation system. For a better understanding, the Blynk app may analyse and display the collected data in the form of graphs, charts, or figures. Improvements in vertical farming communities are predicted to boost grass productivity and quality dramatically.